International epidemic of childhood obesity and television viewing - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2011)
Childhood obesity is one of the most serious global public health challenges of the 21st century. The prevalence of this problem has increased at an alarming rate in many countries. The main causes of childhood obesity are; sedentary lifestyle, unhealthy eating patterns, genetic factors, socio-economic status, race/ethnicity, media and marketing, and the physical environment. Children are clearly being targeted as a receptive market by the manufacturing industry Undoubtedly, television provides one of the most powerful media through which products can be advertised. Furthermore, food advertising accounted for the largest percentage of these advertisements in virtually all countries. Detailed nutritional analysis of food advertisements identified that up to 90% of food products have a high fat, sugar or salt content. Therefore TV viewing is recently identified as one of the risk factors contributing to development of childhood obesity by several mechanisms. This review provides some facts and figures about the global trend of rising obesity among children, amount and content of television and especially food advertisements being watched by children and its possible mechanisms how to cause adverse effects on children's health and contribute to childhood obesity.
Keywords: Television; Obesity; Child; Advertisements; BODY-MASS INDEX; CHILDRENS TELEVISION; PHYSICAL-ACTIVITY; SEDENTARY BEHAVIORS; SLEEP DURATION; US CHILDREN; FAST-FOOD; ADOLESCENTS; PREVALENCE; MEALS